Sunburn in Grapes: A Review - Gambetta, Joanna M.; Holzapfel, Bruno P.; Stoll, Manfred; Friedel, Matthias (Frontiers in Plant Science, 2021)
Sunburn is a physiological disorder that affects the visual and organoleptic properties of grapes. The appearance of brown and necrotic spots severely affects the commercial value of the fruit, and in extreme cases, significantly decreases yield. Depending on the severity of the damage and the driving factors, sunburn on grapes can be classified as sunburn browning or as sunburn necrosis. Sunburn results from a combination of excessive PAR and UV radiation and temperature that can be exacerbated by other stress factors such as water deficit. Fruit respond to these by activating antioxidant defense mechanisms, de novo synthesis of optical screening compounds and heat-shock proteins as well as through morphological adaptation. This review summarizes the current knowledge on sunburn in grapes and compares it with relevant literature on other fruits. It also discusses the different factors affecting the appearance and degree of sunburn, as well as the biochemical response of grapes to this phenomenon and different potential mitigation strategies. This review proposes further directions for research into sunburn in grapes.